THE REFLECTION OF MEDINA CHARTER AS A BASIS FOR RELIGIOUS MODERATION IN INDONESIA - Hamzah, Hamzah (Institut Agama Islam Negeri Bone, 2022)
Religious moderation is a government program that is encouraged in response to the movement of separates, independence, radicalism and terrorism. The existence of religious moderation has been pursued in various spaces as a form of internalization of moderate attitudes in state life. However, it is not impossible that religious moderation drew criticism because it is considered to moderate the Religion of Islam as something final. To urge to highlight religious moderation based on the Medina charter as an embodiment of tolerance. This study aims to describe the reflection of the Medina charter as a basis for religious moderation in managing the country and, in addition, reveal the dimensions of the Medina Charter, which is full of tolerance and moderate values. Meteorologists in this study used a literature method with the conceptual study. The approach used is a theological, historical and sociological approach, with descriptive-analytical analysis methods. The results of this study showed the construction of the Medina charter as a peace treaty and at the same time as the constitution of Medina. The Charter of Medina is referred to as the constitution because it has qualified the form and content of a constitution. The Medina Charter can be called a base of religious moderation. It can be seen from the indicators of religious moderation that they are full of the values of state unity, peace and tolerance. The rhythm of tolerance is evidence of the breath of the Medina charter inherent in religious moderation in heterogeneous cultures.